Effect of the presence of amniotic fluid for optical transabdominal fetal monitoring using Monte Carlo simulations. Issue 9 (19th June 2021) - Gunther, Jacqueline; Jayet, Baptiste; Jacobs, Adam; Burke, Ray; Kainerstorfer, Jana M.; Andersson‐Engels, Stefan
Abstract: About a third of babies are delivered by Cesarean section. There has been an increase in maternal deaths during labor due to complications with subsequent births after a C‐section. Therefore, there is a clinical motivation to reduce the C‐section rate. Current techniques are, however, inefficient at determining fetal distress leading to a high false positive rate for complications and ultimately a C‐section. For the current study, Monte Carlo simulations were used to calculate the amount of signal received on a model of a pregnant mother, as well as, the percent of the signal that comes from the fetal layer. Models with and without a 1 mm amniotic fluid were compared and showed differing trends. Abstract : About a third of babies are delivered by Cesarean section. There is an unmet clinical need to accurately monitor fetal distress in order to reduce the rate of Cesarean section. Here, we use theoretical modeling to understand the effect of the presence of amniotic fluid for transabdominal fetal pulse oximetry by using Monte Carlo simulations.